THE EFFECTS OF PARENTAL FEEDING PRACTICES ON EMOTIONAL EATING IN ADOLESCENTS MEDIATED BY STRESS-RELATED APPRAISAL - CONRAD, TARA LYNN; AYATHUPADY MOHANAN, SANTHOSH (Scholar: Human Sciences, 2022)
This study examined the direct and indirect effect of parental feeding practices on emotional and stress related eating amongst adolescents. The direct impact of parental feeding practices which include parental responsibility, monitoring, pressure to eat and restriction on emotional eating was tested and the indirect impact which includes the mediating roles of Appraisal of Ability & Resources to Cope (AARC) and Appraisal of Outside Stressors and Influences (AOSI). 84 students from 17 different international schools from all over the world participated in the study. The study applied path analysis via multiple regression. Two separate questionnaires were administered to the students. The Children Feeding Questionnaire for Adolescents (CFQ-A) analyzed the student’s perception of their parents feeding practices and the Eating Appraisal Due to Emotional Stress (EADES) Questionnaire evaluated the adolescent’s perception of stressful situations and the impact on stress related eating. Results of the study found that there was not a significant indirect or direct impact on parental feeding behaviors and stress related eating practices amongst students but there was a significant correlation between the mediating factor of Appraisal of Outside Influences perception of outside influences and Stress related eating.